Narrative Review: Implementation of Pharmaceutical Care in Hypertension in Indonesia: Tinjauan Naratif: Penerapan Asuhan Kefarmasian pada Hipertensi di Indonesia - SImamora, Sarmalina; Akbar, Widyan Muchzadi; Mangunsong, Sonlimar (Universitas Tadulako, 2021)
Background: In the past, patient care was not a pharmacy orientation. Several developed countries have applied pharmaceutical care in the treatment of hypertension for years. However, it is still there. In Indonesia, the government issued guidelines for the care of hypertension medications for the first time in 2006. The stages are that pharmacists carry out assessments, prepare pharmaceutical service plans, then implement and monitoring. This study aims to examine the application of pharmaceutical care in hypertension in various articles published in Indonesia. Methods: This research is non-experimental research with a narrative review design. Articles were selected using the keywords pharmaceutical care, pharmacy care, pharmaceutical care and hypertension. Articles in national journals. The number of articles reviewed was 13 articles from 2014 to 2019. Results: The application of pharmaceutical care in hypertension in Indonesia has been carried out by pharmacists, especially in hospitals. The implementation stages are more focused on implementation and monitoring. Only 15% carried out the plan, and almost no carried out the assessment. Conclusion: The application of pharmacy in hypertension has not fully complied with the guidelines. Pharmacists have not assessed when they will start pharmaceutical care. Intervention is carried out with various models, such as leaflets, short messages sent and counselling. Results were monitored on the patient's knowledge, compliance and blood pressure. The result is an improvement, although some are not.